Bioinformatics Analysis for Identifying Differentially Expressed MicroRNAs Derived from Plasma Exosomes Associated with Radiotherapy Resistance in Non-Small-Cell Lung Cancer - Lirong Zeng; Guilin Zeng; Zhong Ye (Applied Bionics and Biomechanics)
Objective. To explore the differentially expressed microRNAs (DEmiRs) derived from plasma exosomes related to radiotherapy resistance and their corresponding pathways in non-small-cell lung cancer (NSCLC). Methods. Plasma samples from NSCLC patients were retrieved and analyzed. The patients were divided into 3 groups based on the tumor regression grade criteria, assessed by radiological imaging after radiotherapy. TRG1 referred to tumor shrinkage of ≤30% after radiotherapy, TRG2 as 30%<TRG<50%, and TRG3 as TRG≥50%. High-throughput sequencing and bioinformatics analysis were used to compare the DEmiRs between the three groups. The miRanda, PITA, and RNAhybrid software were used to identify potential target genes of the DEmiRs. GO function enrichment and KEGG pathway enrichment analyses were performed on the target gene set. Results. There were 24 DEmiRs (12 were upregulated and 12 downregulated) between the TRG1 and TRG2 groups, 11 between the TRG1 and TRG3 groups (6 upregulated and 5 downregulated), and 35 between the TRG2 and TRG3 groups. The common DEmiRs between the three groups were miR-92a-3p. GO analysis showed that the target genes of the DEmiRs were mainly enriched in unicellular organism processes, cell transformation, cell localization, and their establishment. KEGG enrichment analysis showed that target genes were significantly enriched in the Ras signaling pathway and associated with endocytosis. Among the 135 identified target genes of miR-92a-3p, 4 were involved in the PI3K-Akt signaling pathway (the downstream pathway of the Ras gene) and 3 in the cAMP signaling pathway (the upstream pathway of the Ras gene). Further, 2 other target genes were involved in the Rap1 signaling pathway (the upstream pathway of PI3K-Akt). Conclusion. By assessing the expression and functional profile of DEmiRs in the plasma exosomes of NSCLC patients after radiotherapy, miR-92a-3p was identified as a promising target affecting radiotherapy outcomes through the Ras signaling pathway.